A cohort-based analysis of the influence of minimum wage levels on the labor force participation in the informal sector: quantitative and substitution effects (2010)
This paper discuses the effect of the minimum wage on the decision to join the informal job sector. We estimated a pseudo panel of the engagement in the informal sector using an IV-probit. The findings show that an increase in the minimum wage leads to a substitution effect between young and older workers. This results show that the standards effects over the labor market in the WGM segmented model are moderate because an increase of the minimum wage doesn’t imply total mobility between sectors.